Pharmacognostical and Phytochemical Investigations on Ipomoea pes-caprae Linn R. Br. - Ashish Manigauha; N Ganesh; M D Kharya (International Journal of Phytomedicine, 2012)
Ipomoea pes-caprae Linn is commonly used as a first aid to treat jelly-fish stings and in ritual baths to alleviate evil spirits. The leaves were used against pain, inflammation, rheumatism and as stomachic and tonic. The present study was designed to investigate pharmacognosy and phytochemistry of Ipomoea pes-caprae its proper investigation and chemical profiling. Powdered plant extracts were subsequently soxhleted using petroleum ether (60-800C), methanol and water. Swaras was prepared from fresh plant extracts and studied for their phytochemical parameters and freshly prepared powder of I. pes-caprae was studies for its macroscopy for developing its identification parameters. Physicochemical study on I. pes-caprae herb yielded total ash (16.23%), acid insoluble ash (2.16%) and water soluble ash (13.48%) and value for loss on drying was (19.35%). Successive solvent extractive values of its powder were found to be 3.75 % w/w for petroleum ether (60-800C), 5.35 % w/w for methanol and 11.45 % w/w for aqueous extract and the value for swaras was 13.25 % w/w. Phytochemical screening on extracts and swaras revealed the presence of alkaloids, flavonoids, tannins, sterols, terpenoids and glycosides. Pharmacognostic characters, phytochemical values and macroscopic characters taken together as the outcome of this study could be used as the diagnostic tools for identification and standardization of I. pes-caprae for its purity and authencity.